Tourism as a driver of economic development: The Colombian experience - Andreja Benković; Juan Felipe Mejía (Universität Hohenheim, 2008)
The current paper analyzes the importance and potentials of the tourism sector for economic development. It is divided into four major parts. After a short introduction, section two presents some theoretical insights into the topic of economic development. Commenting on the most relevant components of the catching-up theory by Abramovitz (1986) and the structural change theory by Baumol (1967) and others, it could be realized that growth and the accompanying structural changes in the distribution of employment and GDP have their sources in the sector industry. But at the moment of incorporating the demand side explanation of structural change, the service sectors offer growth potentials as well. Furthermore, the basic characteristics and importance of the tourism sector for economic development and employment are emphasized, examining the so-called 'social capabilities' and the innovation potential within the process of economic growth of any nation. A short survey of literature concerning the contribution of this sector to economic growth makes clear that tourism should be considered not just from the perspective of the benefits, but also from the costs associated with it. Section three provides an analysis of the economic impact of tourism in a developing country, namely Colombia, based on time-series analysis and data gathered supported on the 'Tourism Satellite Account' Methodology. Some relevant indicators produced by the World Economic Forum through its 'Travel and Tourism Competitiveness Report', are also evaluated. Finally, some conclusions are drawn with respect to the potentialities, as well as the challenges identified for the Colombian case.
urn:nbn:de:bsz:100-opus-4461
Keywords: L83; L86; L88; O1; O54; Q01; Q5; 330; structural change; service sectors; social capabilities; economic development; tourism; Colombia